PENGARUH HARGA DAN LOKASI TERHADAP KEPUTUSAN KONSUMEN MENGINAP DI HOTEL REDDOORZ NEAR HERMES PLACE POLONIA MEDAN PADA MASA PANDEMI COVID-19 - Desianto Harefa; Mery Lani Purba (JURNAL MUTIARA MANAJEMEN, 2020)
The Covid-19 pandemic has had a considerable impact on the development ofhospitalitybusiness in the country. This resulted in many hotel industries losing money and even temporarily closing hotels until the pandemic was over. The research method used is quantitative data, namely to obtain data and information that will be used as the language of the analyst. The research sample was 83 people. The data collection techniques used were interviews, documentation and distribution of questionnaires at the Reddoorz Hotel Near Hermes Place Polonia Medan. The objectives of this study are: (1) To determine the effect of price on consumer decisions to stay at the Reddoorz Hotel Near Hermes Place Polonia Medan. (2) To determine the effect of location on consumer decisions to stay at the Reddoorz Hotel Near Hermes Place Polonia Medan. (3) To determine the effect of price and location on consumer decisions to stay at the RedDoorz Hotel Near Hermes Place Polonia Medan. The results of this study will show that: (1) There is an effect of price on consumer decisions with a value > > = 5.394> 1.663 with a significant a (0.000 <0.05). (2) There is an effect of location on consumer decisions with a value > > = 4.012> 1.663 with a significant a (0.000 <0.05). (3) There is an effect of price and location on consumer decisions with > > (50.154> 3.11).